The Potential Therapeutic Role of miR-223 in Bovine Endometritis by Targeting the NLRP3 Inflammasome - Zhao, Gan; Jiang, Kangfeng; Yang, Yaping; Zhang, Tao; Wu, Haichong; Shaukat, Aftab; Qiu, Changwei; Deng, Ganzhen (Frontiers in Immunology, 2018)
Bovine endometritis affects milk production and reproductive performance in dairy cows and causes serious economic loss. The underlying molecular mechanisms or signaling pathways of ovine endometritis remain unclear. In this study, we attempted to determine the expression mechanism of mir-223 in endometritis of dairy cows and evaluate its potential therapeutic value. We first confirmed that there was an increased level of miR-223 in endometritis, and then, an LPS-induced bovine endometrial epithelial cell (BEND) line was used to mimic the inflammatory model in vitro. Our data showed that activation of NF-κB promoted the transcription of miR-223, thus inhibiting activation of the inflammatory mediator NLRP3 and its mediation of IL-1β production to protect against inflammatory damage. Meanwhile, in vivo studies showed that inhibition of mir-223 resulted in an enhanced pathology of mice during LPS-induced endometritis, while overexpression of mir-223 attenuated the inflammatory conditions in the uterus. In summary, our study highlights that miR-223 serves both to constrain the level of NLRP3 activation and to act as a protective factor in the inflammatory response and thus provides a future novel therapeutic modality for active flares in cow endometritis and other inflammatory diseases.